Implementing post-diagnostic support for people living with dementia in England: a qualitative study of barriers and strategies used to address these in practice. (6th July 2021) - Wheatley, Alison; Bamford, Claire; Brunskill, Greta; Booi, Laura; Dening, Karen Harrison; Robinson, Louise
Abstract: Background: inequalities and gaps in post-diagnostic support (PDS) for people with dementia persist despite a policy focus on dementia in England and Wales. Understanding and overcoming the factors contributing to these inequalities is vital to improve care for people living with dementia (PLWD) and their families. Objective: to explore common barriers to the delivery of PDS in England and Wales and describe successful strategies to address them, drawing on examples from current practice. Design: qualitative semi-structured interviews, focus groups and observation. Settings: Phase 1: interviewees were drawn from multiple sectors across England and Wales, including NHS clinical commissioning groups and social care. Phase 2: six case study sites based in different sectors (primary care, secondary mental health and third sector) in England. Participants: Phase 1: 61 professionals, including commissioners and service managers. Phase 2: 68 professionals, including frontline staff and those working in related services; 17 PLWD; 31 carers. Results: barriers to implementing PDS in dementia were an unsupportive infrastructure, limited proactive review and limited capacity and capability particularly in primary care. Strategies used successfully in practice to address these challenges included creating opportunities for service development, improving joint working, supporting non-specialists and developing ongoing, holistic review and care planning. Conclusion: a range of practical strategies have been identified to address many of the common barriers to PDS in dementia. To achieve policy goals of a task-shifted and task-shared approach to PDS, widespread use of these strategies is recommended.